2018
DOI: 10.1109/jtehm.2018.2880199
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Clinician Control Interface for a Powered Knee-Ankle Prosthesis: A Case Study

Abstract: This paper presents a potential solution to the challenge of configuring powered knee-ankle prostheses in a clinical setting. Typically, powered prostheses use impedance-based control schemes that contain several independent controllers which correspond to consecutive periods along the gait cycle. This control strategy has numerous control parameters and switching rules that are generally tuned by researchers or technicians and not by a certified prosthetist. We propose an intuitive clinician control interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The addition of tunable parameters provides the ability of easily adopting various walking styles, such as different step lengths or pushoff initiation points, which was not possible in [6]. See [49] for an example of using these tunable parameters in an intuitive clinical control interface.…”
Section: B Limitationsmentioning
confidence: 99%
“…The addition of tunable parameters provides the ability of easily adopting various walking styles, such as different step lengths or pushoff initiation points, which was not possible in [6]. See [49] for an example of using these tunable parameters in an intuitive clinical control interface.…”
Section: B Limitationsmentioning
confidence: 99%
“…This finding is congruent with previous work, as the basis method (and the comparable finite state machine used in this study) are designed to predict average kinematics, with no accommodation for stride-to-stride variance or the specific subject using the prosthesis. Previous work has shown that providing averagesubject kinematics is still an effective method for improving amputee gait [13], [19], and that it is possible, and practical, to tune the kinematic trajectories of individual tasks to better match a subject in a clinical setting [18]. Concurrently, recent work has shown that the continuous format of the basis model can be leveraged to improve the tuning of all tasks, given one tuned task [58].…”
Section: A Kinematic Factors That Affect Model Predictionsmentioning
confidence: 99%
“…Both of these algorithms share the phase and subject individuality kinematic error factors, which are the largest sources of the overall error. If these two factors can be reduced, by tuning and improving the phase variable calculation and employing subject-specific tuning techniques [18], [58], the relative advantage of the basis method would be more significant. Lastly, three of the test tasks in this study matched the available tasks in the state machine exactly.…”
Section: B Comparison To Finite State Machinementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of an emergency, the fixed movement pattern of a person is an instinctive reaction that does not require real-time brain control. The paper proposes the CCI interface adjusting the joint trajectory [16].Therefore, this paper proposes an instinctive human joint trajectory. The joint trajectory is obtained by a Bezier piecewise fitting using the joint trajectory of a healthy individual.…”
Section: Introductionmentioning
confidence: 99%